Apropriações de mídias digitais e dinâmicas de difusão, circulação e consumo da cultura em rede: um estudo netnográfico com bandas independentes de São Luís - MA e Teresina - PI - OLIVEIRA, Walline Alves (2017)
This study aims to analyze the strategies and complexities for music diffusion, circulation and consumption, having as scope the appropriation of communication tools and venues by musicians independent of the cities of São Luis - MA and Teresina - PI; reflect on the impacts of these recent but transformative movements against the new dynamics of culture in the digital era; and, also, to understand strains and challenges of artistic autonomy and independence given the dominant music industry. In our first methodological walkthrough, which was the bibliographical one, we have sought the comprehension about the online culture, associated to the communication practices in the cyberspace. Due to a restructuring in the music industry, opportunities have been opened in which the independent artist and the fans have commenced to act at the core of the process of transmitting and circulating culture in the virtual sphere, due to the appropriations of the current digital communication means. As online sociocultural experiences differ from face-to-face experiences, we have deemed significant to use as methodological contribution to empirical research the online ethnography or netnography. In a qualitative manner, this study does not offer universal generalizations, as it is based on a particular and specific context. Nevertheless, it is understood that this netnographic study can raise theoretical formulations that deepen the understanding of the complex relation established in this context.The online fields studied were three fan pages of independent bands from the cities of São Luis and Teresina. To implement the study, several methods were combined in the netnographic research, among them: direct participant observation in social networking sites, face-to-face interviews, observation - with a specific target - and archival data collections (taken from social network pages of analyzed bands). As a sample, we have had three bands from the independent music scene of the cities aforementioned, whose representatives were interviewed in person at the data collection stage. To analyze the research data, we have followed the proposed criteria for the netnographic study and associated it with two other methods: interviewing analysis and network conversation analysis. After this walkthrough, our study identified, in relation to the analyzed bands, the strategies employed in social networking sites in view of fans' participation and engagement, aiming at achieving network popularity. We also analyzed the difficulties and challenges that the independent musicians of our research have faced in order to circulate their art in cyberspace; we have pointed out that this fact is associated to control mechanisms of the traditional media that are occupying the virtual space. Therefore, the so-called network neutrality can be a utopia that is further and further away from being achieved. Our study is interdisciplinary and the analysis bases are the communication sciences and the computer-mediated communication (CMC), since they are a constituent and decisive part of new habits, sociability manners and social relationship practices, merged into the day-to-day basis of billions of people.